Larvicidal activity of the aqueous extract of the clove (Eugenia caryophyllata) against Aedes aegypti (Diptera, Culicidae) under laboratory conditions. - ES, Medeiros; FM, Costa; IB, Rodrigues; WP, Tadei (Journal of Research in Biology, 2011)
In the search for new agents capable to control the dengue vector, Aedes aegypti, bioassays were performed to assess the larvicidal activity of aqueous extract of clove (Eugenia caryophyllata) under laboratory conditions. Mortality data obtained at 24, 48, and 72 h intervals were subjected to probit analysis to determine the lethal concentrations of the extract. Larval mortality ranged from 43 to 100% among the concentrations were sampled (25 x 103, 50 x 103, 100 x 103, 150 x 103, and 200 x 103 ppm). LC50 and LC90 values were: 29.7 x 103 and 63.5 x 103 ppm for 24 h; 232 x 103 and 39.5 x 103 for 48 h; and 22.0 x 103 and 33.7 x 103 ppm for 72 h, respectively. The LC50 value for the 24 h reading differed from the others by presenting a high chi-square value; therefore, the LC50 value for 48 h was used as reference. These results suggested that the clove extract presents bioactive substances capable of killing mosquito larvae.